A remark on infinite initial values for quasilinear parabolic equations. (May 2020) - Lindqvist, Peter; Parviainen, Mikko
Abstract: We study the possibility of prescribing infinite initial values for solutions of the Evolutionary p -Laplace Equation in the fast diffusion case p > 2 . This expository note has been extracted from our previous work. When infinite values are prescribed on the whole initial surface, such solutions can exist only if the domain is a space–time cylinder.